The phenomenon of jasa titip (jastip) in e-commerce: Analysis of consumer behavior and its growth potential (a case study in Fakfak, West Papua) - Fachruddin, Muh.; Nur, Muhammad; Saputri, Tri Bata Biru (Trigin Publisher, 2026)
Along with the development of technology and the internet, e-commerce has become the primary choice for consumers to obtain goods from outside their regions. However, in remote areas like Fakfak, limited infrastructure often becomes an obstacle in accessing products from outside the region. As a solution, the jasa titip (Jastip) service has emerged, allowing consumers to purchase goods from outside the region through intermediaries, with more efficient shipping costs. This study aims to analyze the phenomenon of Jasa Titip (Jastip) in e-commerce in Fakfak, West Papua, focusing on consumer behavior and its growth potential. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with consumers, Jastip providers, and relevant parties. In addition, observation and documentation were used to strengthen the findings. The results indicate that Jastip actors are motivated by a combination of economic opportunities and community needs due to gaps in product access. Operationally, Jastip in Fakfak has a relatively systematic workflow, but it is still manual and has not been integrated into a digital system. Trust is a key factor in consumer behavior, while service quality and communication play an important role in shaping consumer satisfaction, especially in dealing with logistical limitations and delivery delays. The research findings also show that Jastip in Fakfak has significant growth potential.